Psychopharmacology of chronic aggression and violence in forensic eettings - Cummings, Michael A. (Seminars in forensic psychiatry, 2024)
The goal of this chapter is to show the reader a systematic approach to the assessment and treatment of aggression and violence arising from psychosis and a review of evidence-based pharmacological interventions for aggression and violence arising from impulsivity in the context of traumatic brain injury or neurocognitive disorder. In turn, we consider an algorithmic approach to the assessment and treatment of psychotically driven aggression and violence, the approach to treatment-resistance in schizophrenia spectrum disorders, data-supported treatment of aggression and violence related to traumatic brain injury, and, finally, data-supported pharmacological treatment of aggression and violence in the context of major neurocognitive disorder.